The Importance of Cognitive Ability for Chair of Study Programs in Muhammadiyah University: Urgensi Kepemilikan Kemampuan Kognitif Keprodian Bagi Ketua Program Studi Di Perguruan Tinggi Muhammadiyah - Onny Fitriana Sitorus (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to describe the cognitive ability of study program – the urgently of owned by the head of study program. Research method used is descriptive quantitative with population target/objective throughout the head of study program in the University of Muhammadiyah at Kopertis Region III (now LLDikti Region III, Jakarta-Indonesia). As for the population affordable/limited is the head of study program at Five University of Muhammadiyah on Undergraduate level. Data collection technique using the instrument in the form of tests. The research results showed that the head of study program of the cognitive ability of study program in the category of being. This means the cognitive ability of study program of the head of study program overall proves have the capability in terms of: think, plan, solve problems, understand complex ideas, learn quickly, and learn from experience, related to the duties of the study program. – The urgently of owned of the cognitive ability of study program of the head of study program related to the execution of the study program tasks in ensuring the quality of their courses, all that would be easily realized if the head of study program has positive conditioning Courses i.e. do the work with itqon (a clean, diligent and conscientious).